Dancing on the edge: a journey of living, loving, and tumbling through Hollywood - Tamblyn, Russ; Tomlinson, Sarah, 1976- (Blackstone Publishing, 2024)
"Actor. Artist. Cultural icon. A bold memoir of an extraordinary, singular life lived by one of the worlds most beloved and acclaimed figures: Russ Tamblyn"--Front jacket flap.